FMEA, CAD and CFD INTEGRATED IN THE FIGHT AGAINST THE SARS-Cov 2 PANDEMIC: DEVELOPMENT OF AEROSOL PROTECTIVE APPARATUS FOR PROFESSIONAL DRIVERS: FMEA, CAD e CFD INTEGRADOS NO COMBATE A PANDEMIA DE SARS-Cov 2: DESENVOLVIMENTO DE APARATO PROTETOR CONTRA AEROSSÓIS PARA MOTORISTAS PROFISSIONAIS - Cavaignac, André Luís de oliveira (Brazilian Journal of Production Engineering, 2020)
The SARS-CoV2 pandemic brings to society a group of new challenges related to efforts to combat disease and post-pandemic global return. This work proposes an integrated product development methodology (FMEA+CAD+CFD) to obtain a prototype of an aerosol shield for professional drivers. A new driver aerosol shield CAD prototype was obtained. The FMEA+CAD+CFD methodology was proposed to reduce development time and costs. From the basic development tools, a CAD based prototype was obtained. This initial model supports a FMEA application - to correct failure modes it can be identified and prioritized by the risk priority number. CFD simulation was used to discuss the barrier efficiency. The FMEA can be used to correct prototype in CAD environment – avoid put prototypes in production with inadequacies - and reduces total development time and costs. For products that have fluid dynamics based functions, the failure modes solutions correlated can be helped by CFD simulation - a technique that replaces non-trivial real physical experiments. The FMEA reduces plus to 90% all failure modes RPN in CAD based prototype, after correction actions. CFD simulation shows that the flow lines are strongly deflected by the driver’s shield, compared to no shield situation.